(3GdMGLGJ GdEQTGOjI aj GdeOQSI GdGHJOGFjI aj eMGaXI GdLfhHs - (3SdjeGf, MfGfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2002)
(3SYJ GdOQGSI Edi QUO GdMGLGJ GdEQTGOjI GdehLhOI MGdjG aj dHfGf hNUhUG aj eMGaXI GdLfhH hGdfHWjI, eMOOI CSHGH hfhY GdeTcdGJ GdJj JhGLggG heG EPG cGfJ fSHI GdeTcdGJ GdceqjI hGdfhYjI JNJda MSH fhY GdJYdje hGdeOQSI (B((3QSejI(B- (3NGUI eLGfjI(B- (3NGUI ZjQ eLGfjI(B) (3hMSH GdefWbI GdLZQGajI, Ce Cf ZjGH GdNOeGJ GdEQTGOjI hGdEYOGO GdJQHhj ddeYde jDOj Edi JaGbegG(B. (3gPg GdOQGSI gj LRA ef OQGSI eJcGedI JTed LejY GdeMGaXGJ, dPdc cGfJ GdYjfI bUOjI eDdaI ef (B18 (3eOQSI EHJOGFjI eY eOQGFgG ef eMGaXJj GdLfhH hGdfHWjI, JTed CfhGY GdJYdje GdKdGKI h(B53 (3eYdeG ddeQMdI GdGHJOGFjI ddUa GdQGHY GdCSGSj(B. (3hGSJNOeJ GdeDdaI GdefgL GdhUaj GdJMdjdj, eSJYjfI HYOI COhGJ, cGdGSJeGQI, hHWGbGJ GdYdGeGJ GdeOQSjI dJdGejP GdYjfI, hef Ke JQJjH GdeYWjGJ aj LOGhd hJMdjdgG ceG hfhYG(B. (3LGAJ GdfJjLI eMbbI ddCgOGa cGTaI Yf JCKjQ GdYhGed GdCSQjI hGdGLJeGYjI hGdeOQSjI Ydi GdeSJhi GdJMUjdj ddJdejP, aGJVM Cf GdJdejP GddHfGfj GdLfhHj jYGfj ef UYhHGJ JYdeqjI hGfaYGdjI, aJcqhf YfOg HYV GdeTGcd cGdJCNQ GdOQGSj, GdQShH hGdNLd, NUhUG aj GdeOGQS GdQSejI hGdNGUI GdeLGfjI CcKQ ef GdNGUI ZjQ GdeLGfjI(B. (3ceG Cf GdhVY GdUMj ddJdejP jdYH OhQG cHjQG aj RjGOI GdeTGcd dOjg, EVGaI Gdi eSJhi GdCgd GdJYdjej hGdGbJUGOj GdeJOfj, eeG jhLH VQhQI hLhO eQTO JQHhj aj GdeOGQS hNUhUG YfO XghQ HYV GdeTcdGJ hGdUYhHGJ (B"(3GdSjch(B-(3MQcjI(B" (3HYO GdYOhGf GdESQGFjdj Ydi GdefWbI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle primaire; Elementary Education; Orientation et Conseil; School guidance and counseling; South; Sud; (3GdJhLjg hGdEQTGO GdeOQSjs; (3GdLfhHs; (3GdeQMdI GdGHJOGFjIs